Resolução de problemas na construção de conhecimentos articulados à temática galvanoplastia - SANTOS, Rafael José dos (2019)
The teaching by Transmission-reception corresponds to an insistent reality in Chemistry classrooms, stigmatizing teachers as active subjects in the teaching and learning process while students behave as mere recipients of the contents that are often not articulated with the social contexts in which they are inserted. Intending to contribute to change this scenario, many researchers in Chemistry teaching work to develop and popularize the so-called active teaching methodologies, aiming to prepare teachers to act as mediators of the teaching and learning process, enabling the protagonism of students. In this sense, the teaching by using problem solving represents a valuable strategy that enables the articulation of chemical knowledge with the students' reality, inserting them in scientific research activities in the school context, valuing the problematization, hypothesis elaboration, reflection, debates and the teacher's mediation. Investigations on the teaching and learning of Electroplating point out such content as one of the subjects of greatest difficulty for students to understand. Thus, this research contributed to the construction of concepts related to Electroplating based on Problem-Solving, making use of a teaching and learning sequence. The research subjects, thirty-four high school students from a state school in the metropolitan region of Recife, underwent a diagnostic evaluation containing questions related to the central theme and both the answers of this first evaluation and the answers given as a resolution to the proposed problem were analyzed qualitatively, with a descriptive/interpretative character, aiming to identify the construction of knowledge at a phenomenological, theoretical and representational level. After applying the teaching and learning sequence, it was acknowledged that most students were able to develop the learning of Electroplating in at least two of the three expected levels of chemical knowledge, and it was found that students were able to restructure knowledge to respect the concepts explored in the initial evaluation, especially in relation to the formation of rust, since the students revealed to know it only empirically when they elaborated their answers based on reasoning that took into consideration only the macroscopic observations they had made at some point in their lives. Thus, in addition to verifying the efficiency of the educational product built in this work, a contribution was developed to make it even more evident that the construction of concepts about Electroplating is favored by the problem solving methodology.